2016
DOI: 10.1177/0394632016648176
|View full text |Cite
|
Sign up to set email alerts
|

Safety of implanting sustained-release 5-fluorouracil into hepatic cross-section and omentum majus after primary liver cancer resection

Abstract: This study was designed to evaluate the short-term safety of implanting sustained-release 5-fluorouracil (5-FU) into hepatic cross-section and omentum majus after primary liver cancer resection and its impact on related indexes of liver. Forty patients were selected and divided into an implantation group (n = 20) and a control group (n = 20). On the first day after admission, first week after surgery, and first month after surgery, fasting venous blood was extracted from patients for measuring hematological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
(2 reference statements)
0
6
0
Order By: Relevance
“…Chen et al placed fluorouracil implants on the resection margin of the liver, which only caused an increase in the drainage volume. There were no significant differences in liver function and incidence of bleeding and infection as compared with the control group (21). Another concern about late effect of fluorouracil implants is that the drug carrier was made of nonabsorbable material.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Chen et al placed fluorouracil implants on the resection margin of the liver, which only caused an increase in the drainage volume. There were no significant differences in liver function and incidence of bleeding and infection as compared with the control group (21). Another concern about late effect of fluorouracil implants is that the drug carrier was made of nonabsorbable material.…”
Section: Discussionmentioning
confidence: 78%
“…Besides, there was no significant difference in the incidence of side effects as compared with the control group ( 20 ). Intraperitoneal sustained-release implants have also been used to treat liver cancer ( 21 ) and colorectal cancer ( 22 ) with good outcomes. The present study was a multi-center, randomized, open-label, controlled clinical study that focused on the efficacy and safety of intraperitoneal chemotherapy using fluorouracil implants combined with radical resection and postoperative adjuvant chemotherapy for stage III gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In China, 5-FU is basically used for chemotherapy of GC, colorectal cancer, breast cancer, and pancreatic cancer. Presently, clinical studies on 5-FU sustained-release preparations have focused on colorectal cancer and liver cancer (Cheng et al, 2013;Yuan et al, 2015;Chen et al, 2016;Li et al, 2018), but rarely on GC. The aim of our study was designed to discuss and evaluate the possibilities of radical surgery combined with 5-FU implants in increasing long-term survival rate.…”
Section: Introductionmentioning
confidence: 99%
“…Different from other methods, the use of intraoperative sustained-release 5-FU is promising because of the convenient usage and a long effective time of approximately 1 mo. The use of sustained-release 5-FU implants has shown survival benefits in different types of digestive system tumors such as colon cancer and primary hepatic cellular cancer[ 29 , 30 ]. Furthermore, a few studies on the treatment of gastric cancer, which showed similar results, were also reported by Chinese researchers[ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%